Role of Sport in Promotion of Education at Catholic University of Notre Dame in South Bend, USA - Luković Jablanović, Dragica (Sport - nauka i praksa, 2023)
This paper investigates the value of the Notre Dame University football program for its educational marketing and finances. A strong interdependence between economy, politics, mass media, and sport caused an exceptional popularity of football in the USA. The University of Notre Dame, Indiana was one of the first to adjust to this trend by revitalising its football program which was established as a part of its developmental strategy as early as in 1887. A hypothesis that the popularity of football was successfully used not just for the promotion of education, but also for the further development of the University of Notre Dame has been analysed through the case study methodology. This analysis concludes that the University of Notre Dame boosted its prestige by using its football program as a promotional tool to become one of the highest-ranking research institutions on the national level. On the other hand, this case study confirms that there is no conflict between religious dogma and evidence-based science if they walk together toward the progress, i.e. if their common goal is to set people free.